Predicting role of meaning in life on depression, hopelessness, and suicide risk among Spanish Borderline Personality Disorder patients - García-Alandete, Joaquín; Universidad Católica de Valencia "San Vicente Mártir" (2014)
The relation between the meaning in life and depression, hopelessness, and suicide risk in a sample of Spanish Borderline Personality Disorder patients is analyzed. The hypothesis suggested that meaning in life is a significant negative predictor of these variables. Participed 80 Spanish Borderline Personality Disorder patients (75 women, 5 men) ranged 16-60 years old, M = 32.21, SD = 8.85, from a psychological private practice. Spanish adaptations of the Purpose-In-Life Test, the Beck Depression Inventory-II, the Beck Hopelessness Scale, and the Plutchick’s Suicide Risk Scale were used. Analysis included descriptive, correlations, and simple linear regression. Results showed that Meaning in life was negatively related to depression, hopelessness, and suicide risk. It is necessary to introduce the evaluation of the meaning in life in the assessment of patients with Borderline Personality Disorder and to include in the psychotherapeutic intervention elements to enhance their perception and experience of meaning in life.